Stress at Work. A Special Phenomenon or a Type of General Stress? - Lalević, Nina (Sociološki pregled, 2021)
Occupational stress is drawing the attention of an increasing number of authors who deal with psychology of work and organization. Unlike old, “industrial” definitions of stress at work, modern ones put the emphasis on the psychological aspects of work which have adverse effects on the employee’s mood, motivation and general health condition. Therefore, more attention is dedicated to the approach of superiors, interpersonal relations and balance between private and business life, as well as traditional effects of monotony, work conditions and opportunities for advancement. The author establishes an expertise base about stress by presenting and analyzing the results of numerous scientifically relevant studies on the topic of stress at work, thus familiarizing students, researchers and practitioners with the most important postulates, observations and implications for treating consequences of stress. Moreover, stress as one of the most current issues of modern era is increasingly positioning itself in the centre of the work context through problematic interpersonal relations, conflict or confusing work roles and insufficient or inadequatereward. The author finishes his book/textbook with the chapter about stress measurement methods and techniques, which will be crucial in proving the presence and toxic effects of stress, and in treating stress-related occupational diseases in the future.